Selection of normal spermatozoa with a vacuole‐free head (x6300) improves selection of spermatozoa with intact DNA in patients with high sperm DNA fragmentation rates. (26th June 2012) - Hammoud, I.; Boitrelle, F.; Ferfouri, F.; Vialard, F.; Bergere, M.; Wainer, B.; Bailly, M.; Albert, M.; Selva, J.
Summary Intracytoplasmic morphologically selected sperm injection (IMSI, 6300× magnification with Nomarski contrast) of a normal spermatozoon with a vacuole‐free head could improve the embryo's ability to grow to the blastocyst stage and then implant. However, the most relevant indications for IMSI remain to be determined. To evaluate the potential value of IMSI for patients with a high degree of sperm DNA fragmentation (n = 8), different types of spermatozoa were analysed in terms of DNA fragmentation. Motile normal spermatozoa with a vacuole‐free head selected at 6300× magnification had a significantly lower mean DNA fragmentation rate (4.1 ± 1.1%, n = 191) than all other types of spermatozoa: non‐selected spermatozoa (n = 8000; 26.1 ± 1.5% versus 4.1 ± 1.1%; P < 0.005), motile spermatozoa (n = 444; 20.8 ± 2.7% versus 4.1 ± 1.1%; P < 0.001) and motile, normal spermatozoa selected at 200× magnification (n = 370; 18.7 ± 2.7% versus 4.1 ± 1.1%; P < 0.001) and then motile, morphometrically normal spermatozoa with anterior vacuoles (n = 368; 15.9 ± 2.9% versus 4.1 ± 1.1%; P < 0.05) or posterior vacuoles (n = 402; 22.5 ± 3.6% versus 4.1 ± 1.1%; P < 0.001) selected at 6300× magnification. For patients with high sperm DNA fragmentation rates, selection of normal spermatozoa with a vacuole‐free head (6300×) yields the greatest likelihood of obtaining spermatozoa with non‐fragmented DNA.